2008
DOI: 10.1096/fj.07-105338
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone displacement from mutant cystic fibrosis transmembrane conductance regulator restores its function in human airway epithelia

Abstract: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause cystic fibrosis (CF). The most common mutation, DeltaF508, omits the phenylalanine residue at position 508 in the first nucleotide binding domain (NBD1) of CFTR. The mutant protein is retained in the endoplasmic reticulum and degraded by the ubiquitin-proteasome system. We demonstrate that expression of NBD1 plus the regulatory domain (RD) of DeltaF508 CFTR (DeltaFRD) restores the biogenesis of mature DeltaF508 CFTR protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…Our earlier work and that of Sun et al (35) concluded that the truncation mutants were competing for and displacing ⌬F508 CFTR from key elements in the quality control mechanism, in our case, VCP (19) and HDAC6 and in theirs Aha1 (35). Low temperature rescue of ⌬F508 CFTR allows the processing of immature band B to mature band C but does not correct channel activity (see Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our earlier work and that of Sun et al (35) concluded that the truncation mutants were competing for and displacing ⌬F508 CFTR from key elements in the quality control mechanism, in our case, VCP (19) and HDAC6 and in theirs Aha1 (35). Low temperature rescue of ⌬F508 CFTR allows the processing of immature band B to mature band C but does not correct channel activity (see Fig.…”
Section: Discussionmentioning
confidence: 62%
“…This would contain the complete TMD1 and NBD1. Sun et al utilized a smaller fragment that included only NBD1 and the R domain (35). Given the results from these reports and the data here, the one common element of all these truncated CFTRs is the presence of the NBD1 domain.…”
Section: Discussionmentioning
confidence: 96%
“…PN components facilitating folding of the cytosolic NBD1 and NBD2 are now recognized to include the Hsp40/Hsc-Hsp70 (Meacham et al 1999;Meacham et al 2001;Younger et al 2004;Younger et al 2006;Morito et al 2008;Rosser et al 2008;Grove et al 2009) and Hsp90 chaperone systems (Loo et al 1998;Fuller and Cuthbert 2000;Wang et al 2006;Sun et al 2008;Koulov et al 2010). Calnexin, a membrane-anchored ER-associated chaperone, has been shown to interact with the immature forms of both WT and DF508 vCFTR (Pind et al 1994), although its exact role in folding remains controversial Okiyoneda et al 2002;Amaral 2004;Okiyoneda et al 2004;Norez et al 2006;Okiyoneda et al 2008).…”
Section: Proteostasis In Managing Cystic Fibrosismentioning
confidence: 99%
“…Such transcomplementation does not result in changes in Hsc70 association but is believed to improve F508 CFTR forward folding through intra-and/or inter-molecular domaindomain interactions. A related but distinct approach to promote F508 CFTR maturation is to co-express a fragment of F508 CFTR containing NBD1 and R domains (Sun et al, 2008). This mutant fragment of CFTR can actually sequester key chaperone components from the endogenous F508 CFTR and lead to its rescue.…”
Section: Enhancing F508 Cftr Maturationmentioning
confidence: 99%
“…2). Due to misfolding, F508 CFTR has more extensive association with molecular chaperones (Yang et al, 1993;Jiang et al, 1998;Meacham et al, 1999;Wang et al, 2006;Sun et al, 2008;Roy et al, 2010). Therefore, the impact of chaperone machinery on F508 CFTR is greater than on wild-type CFTR.…”
Section: Chaperone Environment: a Critical But Complex Part Of The Eqmentioning
confidence: 99%